2022
DOI: 10.3899/jrheum.211148
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Uptake Among Individuals With Immune-mediated Inflammatory Diseases in Ontario, Canada, Between December 2020 and October 2021: A Population-based Analysis

Abstract: Objective We assessed COVID-19 vaccine uptake among individuals with immune-mediated inflammatory diseases (IMID) and the Ontario general population. Methods We studied all residents 16 years and older who were alive and enrolled in Ontario's universal health insurance plan as of December 14, 2020 when vaccination commenced (n=12,435,914). Individuals with rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), psoriasis (PsO), and inflammatory bowel disease (IBD) were identified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…16 A study relying on administrative claims data in Ontario, Canada assessed uptake of COVID-19 vaccine as of October 2021 among individuals with several immune-mediated inflammatory diseases (IMID) including rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, psoriasis, and inflammatory bowel disease as compared to the general population. 17 Eighty-two percent of the general Ontario population had received at least one dose of the COVID-19 vaccine, whereas uptake ranged from 87.3% to 90.6% in those with an IMID.…”
Section: Discussionmentioning
confidence: 99%
“…16 A study relying on administrative claims data in Ontario, Canada assessed uptake of COVID-19 vaccine as of October 2021 among individuals with several immune-mediated inflammatory diseases (IMID) including rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, psoriasis, and inflammatory bowel disease as compared to the general population. 17 Eighty-two percent of the general Ontario population had received at least one dose of the COVID-19 vaccine, whereas uptake ranged from 87.3% to 90.6% in those with an IMID.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the immunisation rollout in Ontario has been previously reported. 17 Briefly, due to low vaccine supply, Ontario initially had a slow and low vaccine uptake between December, 2020, and March, 2021, during which time vaccines were prioritised for residents and staff of long-term care and retirement homes, health-care workers, and adults aged 80 years and older. By March, 2021, vaccination of residents was largely prioritised by age (in decreasing age group increments) in rapid succession, resulting in a rapid increase in vaccine uptake of one and two doses among all age groups between March and July, 2021.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…By March, 2021, vaccination of residents was largely prioritised by age (in decreasing age group increments) in rapid succession, resulting in a rapid increase in vaccine uptake of one and two doses among all age groups between March and July, 2021. 17 Administration of third doses started in September, 2021. 18 Most people with immunemediated inflammatory diseases in Ontario were given the BNT162b2 (Pfizer-BioNTech) vaccine (>70%) and the mRNA-1273 (Moderna) vaccine (>18%) as part of their initial two doses, and few patients (<10%) received the Covishield vaccine (also known as ChAdOx1 nCoV-19; Oxford-AstraZeneca).…”
Section: Study Design and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…This was very recently confirmed in a large Canadian study which showed a high COVID-19 vaccine uptake among individuals with immune-mediated inflammatory diseases. 44 …”
Section: Discussionmentioning
confidence: 99%